2023
DOI: 10.3389/fphar.2022.1091018
|View full text |Cite
|
Sign up to set email alerts
|

Wnt signaling pathway-derived score for predicting therapeutic resistance and tumor microenvironment in lung adenocarcinoma

Abstract: Background: Lung adenocarcinoma (LUAD) is the most common subtype of lung cancer. Due to tumor heterogeneity, understanding the pathological mechanism of tumor progression helps to improve the diagnosis process and clinical treatment strategies of LUAD patients.Methods: The transcriptome pattern, mutant expression and complete clinical information were obtained from the cancer genome atlas (TCGA) database and microarray data from gene expression omnibus (GEO) database. Firstly, we used single sample Gene Set E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…FZD family members are a type of seven-pass transmembrane receptor (FZD1-FZD10) that belong to atypical G protein-coupled receptors (GPCRs). Specifically, FZD2 expression was found to associate with the prognosis of LUAD [ 29 ], and promoter CpG methylation of FZD2 might be related to the prognosis of LUSC [ 30 ]. Abnormal expression of many FZDs (FZD3, FZD8 and FZD9) is associated with the development of NSCLC [ 3 ].…”
Section: Aberrant Alterations Of Wnt Components In Nsclcmentioning
confidence: 99%
See 1 more Smart Citation
“…FZD family members are a type of seven-pass transmembrane receptor (FZD1-FZD10) that belong to atypical G protein-coupled receptors (GPCRs). Specifically, FZD2 expression was found to associate with the prognosis of LUAD [ 29 ], and promoter CpG methylation of FZD2 might be related to the prognosis of LUSC [ 30 ]. Abnormal expression of many FZDs (FZD3, FZD8 and FZD9) is associated with the development of NSCLC [ 3 ].…”
Section: Aberrant Alterations Of Wnt Components In Nsclcmentioning
confidence: 99%
“…Abnormal expression of many FZDs (FZD3, FZD8 and FZD9) is associated with the development of NSCLC [ 3 ]. It has been observed that patients with early-stage NSCLC carrying the SNP rs10898563 in FZD4 showed a significant increase in recurrence and mortality risk [ 31 ], and FZD4 expression might be associated with the prognosis of LUAD [ 29 ]. Knockdown of FZD8 by shRNA sensitized the lung cancer cells to chemotherapy [ 32 ].…”
Section: Aberrant Alterations Of Wnt Components In Nsclcmentioning
confidence: 99%
“…Chen’s published work on Oncotarget describes that NKX2-1 may suppress lung adenocarcinoma progression via impeding TGF-β-induced epithelial-to-mesenchymal transition (EMT) due to Elevated expression of E-cadherin and occludin targeted by NKX2-1 impeded migration and induced apoptosis in lung cancer cells. 2327…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21][22] Chen's published work on Oncotarget describes that NKX2-1 may suppress lung adenocarcinoma progression via impeding TGF-β-induced epithelialto-mesenchymal transition (EMT) due to Elevated expression of E-cadherin and occludin targeted by NKX2-1 impeded migration and induced apoptosis in lung cancer cells. [23][24][25][26][27] According to Moeller's published work in Cancer Control journal, patients with lung adenocarcinoma not expressing TTF1 have a worse prognosis. However, the same study also suggests that the administration of the use of immunotherapy in individuals harboring a KRAS mutation and the change from a regimen containing pemetrexed to a regimen containing no pemetrexed, the corresponding patients no longer seem to have a worse prognosis.…”
Section: Introductionmentioning
confidence: 99%